Stable isotope-labeled carnitine reveals its rapid transport into muscle cells and acetylation during contraction. Issue 4 (April 2023) - Furuichi, Yasuro; Goto-Inoue, Naoko; Uchida, Saki; Masuda, Shun; Manabe, Yasuko; Fujii, Nobuharu L.
Abstract: Carnitine plays multiple roles in skeletal muscle metabolism, including fatty acid transport and buffering of excess acetyl-CoA in the mitochondria. The skeletal muscle cannot synthesize carnitine; therefore, carnitine must be taken up from the blood into the cytoplasm. Carnitine metabolism, its uptake into cells, and the subsequent reactions of carnitine are accelerated by muscle contraction. Isotope tracing enables the marking of target molecules and monitoring of tissue distribution. In this study, stable isotope-labeled carnitine tracing was combined with matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) imaging to determine carnitine distribution in mouse skeletal muscle tissues. Deuterium-labeled carnitine (d3-carnitine) was intravenously injected into the mice and diffused to the skeletal muscles for 30 and 60 min. To examine whether muscle contraction changes the distribution of carnitine and its derivatives, unilateral in situ muscle contraction was performed; 60 min muscle contraction showed increased d3-carnitine and its derivative d3-acetylcarnitine in the muscle, indicating that carnitine uptake in cells is promptly converted to acetylcarnitine, consequently, buffering accumulated acetyl-CoA. While the endogenous carnitine was localized in the slow type fibers rather than fast type, the contraction-induced distributions of d3-carnitine and acetylcarnitine were not necessarily associated with muscle fiber type. In conclusion, the combination of isotope tracing and MALDI-MS imaging can reveal carnitine flux during muscle contraction and show the significance of carnitine in skeletal muscles.